2014
DOI: 10.1039/c4ob01419g
|View full text |Cite
|
Sign up to set email alerts
|

The importance of chain conformational mobility during 5-exo-cyclizations of C-, N- and O-centred radicals

Abstract: The reaction coordinates of an archetypical set of 5-exo cyclizations of C-, N-and O-centred radicals were investigated by computational methods. G4 theory, and DFT with the um062x functional, were able to rationalise counterintuitive factors such as the 'normal' order of rate constants being: N-centred < C-centred < O-centred radicals. The access angle between the radical centre and the double bond was identified as a key factor. Examination of its evolution during ring closure implied that rigidity at the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Apart from the reduction potential of the conduction band, conformational mobility in the intermediate 145 plays an important role in the competition between these two reactions. [96] The same reaction was also observed under UV irradiation and without a photoredox catalyst. [97] Under these conditions, only tandem addition cyclization products were obtained.…”
Section: C-c Bond Formationsupporting
confidence: 56%
“…Apart from the reduction potential of the conduction band, conformational mobility in the intermediate 145 plays an important role in the competition between these two reactions. [96] The same reaction was also observed under UV irradiation and without a photoredox catalyst. [97] Under these conditions, only tandem addition cyclization products were obtained.…”
Section: C-c Bond Formationsupporting
confidence: 56%
“…The computational investigation of these trends suggested that increased rigidity of reacting nitrogen species can be the reason for this counterintuitive order . Interestingly, the computational data suggest that carbon centered radicals engage in the bond forming interactions with the target π‐bond at the larger distances than their nitrogen and oxygen analogues.…”
Section: Manipulation Of Selectivitiesmentioning
confidence: 99%
“…[9] While facing the difficulties of developing cascade photoredox imino functionalizations of electron-poor O-aryl oximes, [6] we realized that an inherent chemical reactivity issue was associated with the envisaged catalytic cycle.T he nitrogen radicals A are electrophilic species and undergo facile exo-trig cyclizations (Scheme 1C). [10] However,u pon ring closure,they generate the nucleophilic carbon radical B, which benefits from polar effects [11] in the reaction with SOMOphiles X À Y. This process leads to the formation of the imino-functionalized product C and the radical YC.T his radical, even though it is not involved in any bond-forming event, controls the fate of our photoredox manifold.…”
mentioning
confidence: 99%